Unveiling the Dynamics of Ethiopian Defence Diplomacy: A Focus on Peacekeeping Contributions - Sigatu, Kaleab Tadesse (European Scientific Journal, ESJ, 2024)
This paper mainly addresses Ethiopia’s defence diplomacy through its participation in peace support operations. This qualitative research study aims to analyze and synthesize the findings from relevant literature reviews to show to what extent Ethiopia has used peacekeeping participation as a tool of defence diplomacy in contributing to peace and security, especially in the Horn of Africa region. The paper finds that Ethiopian defence diplomacy is essential for Ethiopia to achieve its global foreign policy objectives, promote regional stability and cooperation, and seek regional influence.